2020
DOI: 10.3892/or.2020.7505
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of exosomal miR‑29s in peritoneal fluid is a useful predictor of peritoneal recurrence after curative resection of gastric cancer with serosal involvement

Abstract: The peritoneal surface is the most frequent site of metastasis disease in patients with gastric cancer. Even after curative surgery and adjuvant chemotherapy, peritoneal recurrences often develop. Exosomes play pivotal roles in tumor metastasis via the transfer of microRNAs (miRNAs). In the present study, exosomes were isolated from peritoneal lavage fluid or ascites in 85 patients with gastric cancer and the relative expression levels of miR-29s were examined. The expression of miR-29a-3p, miR-29b-3p and miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 46 publications
(51 reference statements)
1
32
0
Order By: Relevance
“… 24 EXs can shuttle their cargos of proteins, mRNAs, and miRNAs between cells, and EXs secreted from cancer cells can have effects on the tumor microenvironment. 25 In the current study, the obtained findings revealed that exosomal miR-181a from hypoxia-induced PTC cells enhanced angiogenesis and tumor growth by downregulation of MLL3 and DACT2 and upregulation of YAP and VEGF signaling.…”
Section: Discussionsupporting
confidence: 54%
“… 24 EXs can shuttle their cargos of proteins, mRNAs, and miRNAs between cells, and EXs secreted from cancer cells can have effects on the tumor microenvironment. 25 In the current study, the obtained findings revealed that exosomal miR-181a from hypoxia-induced PTC cells enhanced angiogenesis and tumor growth by downregulation of MLL3 and DACT2 and upregulation of YAP and VEGF signaling.…”
Section: Discussionsupporting
confidence: 54%
“…Studies show that miRNA can be identified in serum-circulating exosomes, allowing the staging of patients. For example, exosomes containing miR-29s are found to play a suppressive role in the growth of peritoneal-disseminated tumour cells and are under-expressed in patients with peritoneal metastases [ 115 ]. Low expression of this miRNA in exosomes is correlated to bad prognosis of patients.…”
Section: Biomarkers and Therapeutic Strategiesmentioning
confidence: 99%
“…Research advances in GC-derived peritoneal exosomes have involved the examination of exosomal biomarkers in peritoneal fluid. Recently, reduced expression of exosomal miR-29s were found to be associated with synchronous PD and PD recurrence in GC with serosal involvement [127].…”
Section: Molecular Markers In Peritoneal Lavagesmentioning
confidence: 99%